The early stories of Truman Capote - Capote, Truman, 1924-1984 (Random House, 2015)
"In a small Southern town, a teenage girl anxiously waits for her date to arrive. A little boy meets his dream dog in Central Park. A woman fights to save the life of a child who has her lover's eyes. Best friends discuss the theoretical murder of husbands. In these never-before-published stories, written by Truman Capote when he was in his teens and twenties, Capote-the-Writer is already recognizable. His prose: witty, poignant, and crystal-clear. His characters: solitary, observant young children; charming and naïve young women whom you could imagine befriending Holly Golightly; aging urban sophisticates worn down by cynicism. His settings: the rural South of his childhood and the cosmopolitan New York of the 1940s. This splendid collection offers readers to opportunity to see the confident first steps of one of the 20th century's most-acclaimed writers onto the path that would lead to his most beloved works"--